Overview: Development of the National Ignition Facility and the Transition to a User Facility for the Ignition Campaign and High Energy Density Scientific Research. (1st February 2016) - Moses, E. I.; Lindl, J. D.; Spaeth, M. L.; Patterson, R. W.; Sawicki, R. H.; Atherton, L. J.; Baisden, P. A.; Lagin, L. J.; Larson, D. W.; MacGowan, B. J.; Miller, G. H.; Rardin, D. C.; et al.
Abstract: The National Ignition Facility (NIF) at Lawrence Livermore National Laboratory has been operational since March 2009 and has been transitioning to a user facility supporting ignition science, high energy density stockpile science, national security applications, and fundamental science. The facility has achieved its design goal of 1.8 MJ and 500 TW of 3ω light on target, and has performed target experiments with 1.9 MJ at peak powers of 410 TW. The National Ignition Campaign (NIC), established by the U.S. National Nuclear Security Administration in 2005, was responsible for transitioning NIF from a construction project to a national user facility. Besides the operation and optimization of the use of the NIF laser, the NIC program was responsible for developing capabilities including target fabrication facilities; cryogenic layering capabilities; over 60 optical, X-ray, and nuclear diagnostic systems; experimental platforms; and a wide range of other NIF facility infrastructure. This paper provides a summary of some of the key experimental results for NIF to date, an overview of the NIF facility capabilities, and the challenges that were met in achieving these capabilities. They are covered in more detail in the papers that follow.